An Optimum Technique for Renewable Power Generations Integration to Power System Using Repeated Power Flow Technique Considering Voltage Stability Limit - Chaisit Wannoi; Anurak Khumdee; Narumon Wannoi; Chai / Chow Chompoo-inwai (My University, 2016)
This paper presents an optimum location definition and technique for a better placement location of renewable power generations in a wide area power system using repeated power flow technique considering voltage stability limit. In this study, for a better understanding, the author have implemented the newly proposed idea on Thailand's power system especially focusing on renewable generation support plan from the government policy under the current Power Development Plan (PDP 2015). The study results have compared between: 1) installation the renewable generation at the newly recommendation area and 2) installation the renewable generation facilities throughout into distribution system in the Northeastern area of Thailand. The study results focus on impaction to voltage stability when system has load demand increasing and generation capacity decreasing. This study, a Modified-Thailand's power system during peak load in 2013 was used as a system base case with generation capacity around 27,400 MW and load demand around 26,810 MW while system losses 590 MW. The results found that the newly proposed technique can define optimum location for install renewables generation in wide area to enhance system security in term of voltage stability impaction. This technique may also carry to define the installation of other equipment as FACTS devices or define generation dispatch for Automatic Generation Control system (AGC) for power system stability enhancement.
Keywords: Optimal Power Flow Distribution